2014
DOI: 10.4103/0972-0707.144567
|View full text |Cite
|
Sign up to set email alerts
|

Root canal centering ability of rotary cutting nickel titanium instruments: A meta-analysis

Abstract: Aim:To systematically review articles on canal centering ability of endodontic rotary cutting Nickel-Titanium (Ni-Ti) instruments and subject results to meta-analysis.Materials and Methods:A comprehensive search was initiated on canal centering ability of different rotary cutting Ni-Ti files such as Protaper, Hero Shaper, K3, Mtwo, Race, Wave One by selecting articles published in peer reviewed journals during 1991-2013 using “Pub Med” database. Inclusion and exclusion criteria were established. A data was cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 15 publications
0
24
0
1
Order By: Relevance
“…Although these variations are valuable in providing different alternatives that can cope with the variations in the root canal system, however, the performance of these instruments inside each canal is not always predictable. [3][4][5] The invention of the NiTi rotary instrumentation was advantageous in minimizing the procedural errors and time of treatment. 6 A new technique for instrumentation was introduced by Yared, where a single file was used in a reciprocating motion rather than rotation, overcoming the large sequence of files used in a rotation motion.…”
Section: Introductionmentioning
confidence: 99%
“…Although these variations are valuable in providing different alternatives that can cope with the variations in the root canal system, however, the performance of these instruments inside each canal is not always predictable. [3][4][5] The invention of the NiTi rotary instrumentation was advantageous in minimizing the procedural errors and time of treatment. 6 A new technique for instrumentation was introduced by Yared, where a single file was used in a reciprocating motion rather than rotation, overcoming the large sequence of files used in a rotation motion.…”
Section: Introductionmentioning
confidence: 99%
“…The possible reason might be as SAF has flexible and compressible hollow tube which adapts to canal anatomy and due to its scrapping action it removed minimal circumferential dentin than protaper rotary. [12,13] In the present study, SAF was centered in both bucco lingually and mesio distally. The possible reason might be due to its file and scrapping action.…”
Section: Discussionmentioning
confidence: 47%
“…Afterwards, a dynamic FEA was proposed for the visualization of the instrument mechanical stresses during shaping [17][18][19][29][30][31][32]. In all these studies, the differences found between the instruments were due to the geometry of the instruments and to the alloy stiffness: especially, it was demonstrated how the most rigid instruments caused the highest stress on the apical portion of the canal, confirming that these two instrument characteristics influence their mechanical behavior [4,19,26,33,34].…”
Section: Discussionmentioning
confidence: 95%
“…Instrument alloy and other geometrical variables influence the shaping behavior of the endodontic files [1,2,[4][5][6]9,10,12]. The super-elasticity of modern NiTi instruments reduces the occurrence of canal aberrations and allows for a more centered root canal preparation [9,10,26]. Canal centering ability is essential to provide a less invasive shaping, without removing exceeding radicular structure [27,28].…”
Section: Discussionmentioning
confidence: 99%